Low‐Dose Thyroxine Attenuates Autism‐Associated Adverse Effects of Fetal Alcohol in Male Offspring's Social Behavior and Hippocampal Gene Expression. (13th June 2013) - Tunc‐Ozcan, Elif; Ullmann, Timothy M.; Shukla, Pradeep K.; Redei, Eva E.
Abstract : Background: Fetal alcohol spectrum disorder (FASD) is characterized by neurodevelopmental anomalies manifesting in cognitive and behavioral deficits in the offspring with diverse severities. Social behavior is affected in FASD, and these deficits overlap with those of autism spectrum disorder (ASD). Identifying some of the molecular characteristics related to ASD in an animal model of FASD could ultimately provide details on the underlying molecular mechanisms of both disorders that could lead to novel treatments. Methods: Pregnant Sprague–Dawley rats received the following diets: control (C; ad libitum standard laboratory chow), nutritional control pair‐fed (PF), ethanol (EtOH), or an EtOH diet supplemented with 0.3, 1.5, or 7.5 mg thyroxine (T4)/l in the diet. Social behavior and memory were tested in the adult offspring. Plasma total T4, free T3 (fT3), and thyroid‐stimulating hormone (TSH) levels were measured. Hippocampal expression of Gabrb3, Ube3a, Nr2b, Rasgrf1, and Dio3 were measured by RT‐qPCR and protein levels of Mecp2 and Slc25a12 by Western blotting. Results: Adult male offspring of EtOH dams showed elevated fT3 and low TSH levels. Adult male, but not female, offspring of EtOH dams exhibited social behavior and memory deficits. Expression of autism candidates, Gabrb3, Ube3a, Mecp2, and Slc25a12, was significantly increased in the hippocampus of male offspring of EtOH dams. Hippocampal Nr2b and Dio3 were also increased, while Rasgrf1 was decreased in the same population. Peripheral thyroid function, social behavioral deficits, and altered expression of the above genes were normalized by simultaneous administration of 0.3 mg/l T4 in the EtOH diet. Conclusions: Our data suggest that social interaction deficits of FASD share molecular mechanism with ASD by showing altered hippocampal expression of several ASD candidate genes. Social interaction deficits as well as the gene expression changes in the offspring of EtOH‐consuming dams can be reversed by low dose of thyroid hormone supplementation to the mothers.